Hepatic Stellate Cell-Derived Microvesicles Prevent Hepatocytes from Injury Induced by APAP/H2O2 - Renwei Huang; Qunwen Pan; Xiaotang Ma; Yan Wang; Yaolong Liang; Bingyan Dai; Xiaorong Liao; Mingyi Li; Huilai Miao (Stem Cells International)
Hepatic stellate cells (HSCs), previously described for liver-specific mesenchymal stem cells (MSCs), appear to contribute to liver regeneration. Microvesicles (MVs) are nanoscale membrane fragments, which can regulate target cell function by transferring contents from their parent cells. The aim of this study was to investigate the effect of HSC-derived MVs on xenobiotic-induced liver injury. Rat and human hepatocytes, BRL-3A and HL-7702, were used to build hepatocytes injury models by n-acetyl-p-aminophenol n-(APAP) or H2O2 treatment. MVs were prepared from human and rat HSCs, LX-2, and HST-T6 and, respectively, added to injured BRL-3A and HL-7702 hepatocytes. MTT assay was utilized to determine cell proliferation. Cell apoptosis was analyzed by flow cytometry and hoechst33258 staining. Western blot was used for analyzing the expression of activated caspase-3. Liver injury indicators, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lactate dehydrogenase (LDH) in culture medium were also assessed. Results showed that (1) HSC-MVs derived from LX-2 and HST-T6 were positive to CD90 and annexin V surface markers; (2) HSC-MVs dose-dependently improved the viability of hepatocytes in both injury models; (3) HSC-MVs dose-dependently inhibited the APAP/H2O2 induced hepatocytes apoptosis and activated caspase-3 expression and leakage of LDH, ALT, and AST. Our results demonstrate that HSC-derived MVs protect hepatocytes from toxicant-induced injury.